The Nonthermal Emission Following GW170817 is Consistent with a Conical Radially Stratified Outflow with Initial Lorentz Factor ≲10 - Gilad Sadeh; Eli Waxman (The Astrophysical Journal, 2025)
We show that the nonthermal radio to X-ray emission following the neutron star merger GW170817 is consistent with synchrotron emission from a collisionless shock driven into the interstellar medium (ISM) by a conical radially stratified outflow observed ≈0.25 rad off-axis, with a power-law mass dependence on momentum, M (> γβ ) ∝ ( γβ ) ^−4 , maximum Lorenz factor γ = 10, opening (half-)angle ≈0.15 rad, and total energy of ≈5 × 10 ^50 erg. The temporal dependence of the flux during its rising phase is determined by the radial stratification structure, which determines the rate at which outflow energy is deposited in the ISM. This is in contrast with highly relativistic, γ ≈ 100, structured jet models, where the angular jet structure determines the time dependence through the gradual “unveiling” by deceleration of larger angular sections of the jet (which are initially “hidden” by relativistic beaming), typically leading to a predicted flux decline after the peak that is faster than observed. Our model predicts a dependence on the observing angle, which is different than that predicted by highly relativistic jet models. Particularly, similar merger events observed closer to the symmetry axis are predicted to show a similarly extended duration of flux increase with time. Our analysis demonstrates that the data do not require a highly relativistic γ ≈ 100 component, but the presence of such a component with opening angle ≪0.15 rad and energy ≪5 × 10 ^50 erg cannot be excluded.